Analisis Komposisi dalam Postingan Kata Mutiara di Media Sosial Instagram - Rengki Afria; Dian Fitriani (Kajian Linguistik dan Sastra, 2023)
This study examines the analysis of composition in pearls posting on social media Instagram. The purpose of this study (1) to find out what kinds of compound words are used in posting pearls of wisdom on Instagram (2) explain the meaning contained in these compound words. This research uses a qualitative approach with descriptive methods. The stages of data collection are using listening techniques, documentation and note taking techniques. Stages of data analysis, using the method of distribution with basic techniques, namely techniques for Direct Elements (BUL). The data source is aphorisms contained in the caption on Instagram as many as the caption taken in April 2020. Based on the results of the study, found three types/forms of composition analyzed by category, namely the noun, verb, and adjective categories.Based on the class of constituent elements there are six forms of the fifteen data found, namely five data formed from nouns (N) + nouns (N); two data are formed from Adjectives (Adj) + Verbs (V); four data formed from nouns (N) + adjectives (adj); two data are formed from Adjectives (Adj) + Nouns (N), one data is formed from Verbs (V) + Nouns (N); and one data formed from nouns (N) + verbs (V). Abstrak Penelitian ini mengkaji tentang analisis komposisi dalam postingan kata mutiara di media sosial instagram. Tujuan penelitian ini (1) mengetahui jenis kata majemuk apa saja yang digunakan dalam postingan kata mutiara di instagram (2) menjelaskan makna yang terkandung dalam kata majemuk tersebut. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Tahapan pengumpulan data yakni menggunakan teknik simak, dokumentasi dan teknik catat. Tahapan analisis data menggunakan metode agih dengan teknik dasar, yaitu teknik Bagi Unsur Langsung (BUL). Sumber data adalah kata-kata mutiara yang terdapat pada caption di instagram sebanyak caption yang diambil pada bulan April 2020. Berdasarkan hasil penelitian, ditemukan tiga jenis/ bentuk komposisi yang dianalisis berdasarkan kategorinya, yaitu kategori nomina, verba, dan adjektiva. Berdasarkan kelas kata unsur pembentuknya terdapat enam bentuk dari lima belas data yang ditemukan, yaitu lima data terbentuk dari Kata Benda (N) + Kata Benda(N); dua data terbentuk dari Kata Sifat (Adj) + Kata Kerja (V); empat data terbentuk dari Kata Benda (N) + Kata Sifat (Adj); dua data terbentuk dari Kata Sifat (Adj) + Kata Benda(N), satu data terbentuk dari Kata Kerja (V) + Kata Benda (N); dan satu data terbentuk dari Kata Benda (N) + Kata Kerja (V).